The first ten years: how our graduates and students view the HOU M.Ed. in TESOL programme. - Sophia Papaefthymiou-Lytra; Nicos Sifakis (Research Papers in Language teaching and Learning, 2011)
On the occasion of the tenth anniversary of the Μ.Ed. in TESOL programme of the Hellenic Open University, we distributed a questionnaire to graduates as well as current students of the programme. Our primary goal was to further reflect on the usefulness of the programme ten years after and identify possible weak points that need enhancement for the ultimate benefit of our students and the Greek society at large. To that end, we aimed to map out students’ views about the programme and its influence on their professional life. In the various sections of the questionnaire we tried to explore (a) whether their expectations are fulfilled; (b) which modules of those on offer they have selected and which they consider as the most and least important for their professional training and development; (c) how the programme has influenced the professional choices they make/have made outside teaching a class-proper; (d) whether they regard the programme as a springboard for further professional development which they can embark upon on their own; (e) what suggestions they can make for the programme’s further improvement of. The results were very positive. The goals we had set forth in 1998, when this Μ.Ed. in TESOL teacher education programme was inaugurated, were definitely fulfilled for the benefit of the teachers of English at large both in the private and the state sector. The work that has been carried out so far points to a bright future, provided we continue on the same successful course and implement all necessary changes and adjustments required by our changing times.